TELEVISI BESERTA REALITAS NILAI MEDIANYA - Arief Agung Suwasono (DeKaVe, 2011)
Television is a medium that delivers meaning through various type of text television conveys information that promotes moral responsibility and social solidarity. In spite of the fact that television is one of capitalism product, its programs can generate social commitment and solidarity reflecting human moral values.Keyword : Television, Fetisme